The Idiosyncratic Archive: Queerness, Duration and Photography - Rogerson, Steph Schem (Identities: Journal for Politics, Gender and Culture, 2018)
Author(s): Steph Schem Rogerson Title (English): The Idiosyncratic Archive: Queerness, Duration and Photography Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 94-101 Page Count: 8 Citation (English): Steph Schem Rogerson, “The Idiosyncratic Archive: Queerness, Duration and Photography,” Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018): 94-101.